"Narratives of Modernity: Creolization and Early Postcolonial Style in Thomas Mofolo's Chaka". (23rd March 2018) - Sides, Kirk B.
Abstract : This article revisits Thomas Mofolo's novel Chaka (1925) in order to make an argument for a different historical approach to the field of African literatures. Often called one of the earliest African novels, I argue that how we read Chaka – especially for what Simon Gikandi calls the novel's "early postcolonial style" – is indicative of a range of assumptions about Africa and its relationship to modernity. In the article, I explore some of the ways in which Chaka has been made to give precedence to other and mostly subsequent imaginings of both the African postcolonial struggle, as well as African ideas on modernity and national culture. Also, through a brief comparison with Chinua Achebe's foundational Things Fall Apart, the article explores the possibilities of an African discourse on creolization in Chaka, a discourse that rejects the European colonial-encounter narrative of African and postcolonial modernity.